Reverse triage: a systematic review of the literature - Pollaris, Gwen; De Bondt, Frieda; Sabbe, Marc (Frontiers in Disaster and Emergency Medicine, 2023)
Background Many techniques to increase hospital surge capacity in the case of a mass casualty incident (MCI) have already been studied, but a new technique, reverse triage, has gained attention. The objective of this systematic review is to provide a comprehensive literature overview regarding the use of the reverse triage principle in emergency and disaster medicine. Methods A systematic literature review was carried out adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Publications up to May 2023 in the Medline, Embase, CENTRAL, CINAHL, and Web of Science databases were considered. The risk of bias was assessed using the Methodological Items for Non-Randomized Studies, the Risk of Bias Assessment Tool for Systematic Reviews, and Johanna Briggs Institute tools for observational, systematic reviews, and expert opinions respectively. Results The initial search identified 21,259 unique records, of which 16 were included, consisting of 2 reviews, 5 expert opinions, and 9 observational studies. Across studies, an overall surge capacity of 20–30% could be achieved by implementing reverse triage and even more when combined with other strategies. Furthermore, the American framework that comprehended a safe discharge protocol for inpatients is being used in the development of new reverse triage discharge protocols. The risk of developing a complication (adverse event) due to early discharge is rather low. Discussion Due to the heterogeneity of the included studies, the interpretation of the results should be taken with caution. The most prominent differences were related to study size, university affiliation, health care system, and patient characteristics. Nevertheless, implementing the reverse triage principle in MCIs to guide early discharge of adult inpatients can create additional surge capacity with a minor occurrence of adverse events. A final assessment by a multidisciplinary discharge team (nurses and physicians) remains crucial. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022294136, identifier: CRD42022294136.